Rare widespread dissemination of cervical high-grade squamous intraepithelial lesion with microinvasive squamous cell carcinoma: a case report - Liu, Shijie; Liu, Dan (Frontiers in Oncology, 2025)
BackgroundCervical high-grade squamous intraepithelial lesion (HSIL), a precancerous condition, can progress to cervical squamous cell carcinoma (CSCC), the most prevalent histological subtype of cervical cancer. Although CSCC most commonly metastasizes via lymphatic or hematogenous routes, contiguous superficial spread to the endometrium, fallopian tubes, and ovaries is rare.Case presentationA 61-year-old postmenopausal woman was referred to our hospital for further evaluation after a positive HPV-16 test and normal ThinPrep Cytologic Test (TCT) results during a routine health examination at an external institution two weeks earlier. Histopathological examination of colposcopy-guided biopsies confirmed chronic cervicitis with HSIL. Notably, the serum squamous cell carcinoma antigen (SCC-Ag) level was markedly elevated (32.20 ng/mL). Transvaginal color Doppler ultrasonography revealed a cystic mass in the right pelvic region. Intraoperative laparoscopic findings included a tortuous, thickened right fallopian tube with fimbrial occlusion. Gross pathological examination revealed an irregular grayish-white endometrial lesion measuring 2.5*2.0 cm. The right fallopian tube exhibited focal dilation, measuring 1.6 cm in diameter. No gross abnormalities were detected in the right ovary. Final histopathology confirmed extensive cervical HSIL (CIN III) with multifocal stromal invasion (maximum depth: 4 mm), which involved the endometrium, right fallopian tube mucosa, and an ovarian inclusion cyst on the ipsilateral side.ConclusionCervical HSIL/SCC may exhibit superficial upward extension to the endometrium and, in rare cases, can involve the ovaries. Although rare, this clinical entity warrants increased clinical vigilance. Currently, no standardized management guidelines exist for this distinct metastatic pattern, and emerging evidence suggests a multifactorial pathogenesis. These findings underscore the need for enhanced early detection and preventive strategies.